Genetic segregation analysis of familial mitral valve prolapse shows no linkage to fibrillar collagen genes. Issue 3 (March 1989) - Wordsworth, P; Ogilvie, D; Akhras, F; Jackson, G; Sykes, B
Abstract : Three pedigrees were identified in which mitral valve prolapse seemed to be inherited as a mendelian autosomal dominant trait. The segregation of the genes encoding the major fibrillar collagens present in valve tissue, collagens I and III, was analysed by use of restriction enzyme site variants as genetic markers. In one pedigree there was discordance between the segregation of the disease and markers for all three collagen genes. In another, there was discordance between the disease and markers for both collagen I loci. This is evidence against the disease being generally the result of mutations of the genes encoding the major fibrillar collagens.